RANCANG BANGUN SISTEM DAFTAR HADIR BERBASIS FINGERPRINT DENGAN ARDUINO UNO - Kadek Laksmi Damayanth; I Made Agus Widiana Putra; I Putu Buda Suyasa (Universitas Tabanan, 2023)
Recording attendance is an important factor in the management of human resources. Information regarding attendance that can determine achievement, productivity or progress of the agency. So we need a smart attendance system that can work automatically, with a design method that makes a smart attendance system using fingerprint technology and using a control system. Data in the form of unique strokes at the fingertips of every human being is used as data. When this fingerprint is attached to the attendance device, the data is automatically entered into the Arduino. The results of this study indicate that Arduino Uno can be used as an attendance system controller using a fingerprint sensor. The FMP10 fingerprint sensor can read as many as 127 fingerprint data. This design was made to facilitate attendance automatically by attaching fingerprints to the fingerprint sensor and data will enter automatically into the Arduino without having to use stationery, pens, attendance books, and enter attendance data manually, so the impact of this design is good for use. because it is quite easy to use compared to manually.